Hydrothermal Alteration on Composite Volcanoes: Mineralogy, Hyperspectral Imaging, and Aeromagnetic Study of Mt Ruapehu, New Zealand. (5th September 2020) - Kereszturi, Gabor; Schaefer, Lauren N.; Miller, Craig; Mead, Stuart
Abstract: Prolonged volcanic activity can induce surface weathering and hydrothermal alteration that is a primary control on edifice instability, posing a complex hazard with its challenges to accurately forecast and mitigate. This study uses a frequently active composite volcano, Mt Ruapehu, New Zealand, to develop a conceptual model of surface weathering and hydrothermal alteration applicable to long‐lived composite volcanoes. The alteration on Mt Ruapehu was classified using ground samples as non‐altered, supergene argillic, intermediate argillic, and advanced argillic. The first two classes have a paragenesis that is consistent with surficial infiltration and circulation of low‐temperature (<40°C) neutral to mildly acidic fluids, inducing chemical weathering and formation of weathering rims on rock surfaces. The intermediate and advanced argillic alteration formed from hotter (≥100°C) hydrothermal fluids with lower pH, interacting with the andesitic to dacitic host rocks. The distribution of weathering and hydrothermal alteration has been mapped with airborne hyperspectral imaging through image classification, while aeromagnetic data inversion was used to map alteration to up to 500‐m depth. The joint use of hyperspectral imaging complements the geophysical methods since it can spectrally identify hydrothermal alteration mineralogy. This study established a conceptual model of hydrothermal alteration history of Mt Ruapehu, exemplifying a long‐lived and nested active and ancient hydrothermal system. This study's combination approach can be used to indicate the most likely sources of future debris avalanches, which are a significant hazard on Ruapehu. Plain Language Summary: Groundwater heated by shallow molten rock and volcanic gases beneath a volcano can become acidic. When the acidic groundwater rises to the surface, it chemically interacts with volcanic rocks. This interaction turns the rocks and thus the volcano weaker (e.g., replacement of original mineralogy by softer clay minerals), making the edifice more susceptible to collapse. This study integrates geological, remote sensing and geophysical methods to understand the hydrothermal alteration history of Mt Ruapehu, New Zealand. The rock samples collected indicate different minerals associated with alteration processes due to acidic groundwater. Hyperspectral imaging, which measures reflected radiation from the Earth's surface at hundreds of wavelengths, was used to map the distribution of the surface mineralogy using image classifications. The underground distribution of the weak rocks was identified using aeromagnetic surveys. Aeromagnetic data are sensitive to iron‐bearing minerals that are often dissolved by hydrothermal fluids, leaving low magnetic anomalies distributed underground at Mt Ruapehu. Based on the combination of these methods, we propose a new conceptual model for the alteration history of Mt Ruapehu during the last 200, 000 years, contributing to a fuller assessment of natural hazards associated with large‐scale landslides. Key Points: Surface weathering and hydrothermal mineralogy were constrained using VNIR and SWIR reflectance spectroscopy and SEM‐EDS analysis Combination of airborne hyperspectral image analysis and aeromagnetic data inversion mapped surface and buried hydrothermal alteration on Mt Ruapehu volcano Complex spatial and temporal hydrothermal evolution of Mt Ruapehu is revealed